Linear phase delay detection method for optical voltage transformer based on S-wave plate. (19th May 2021) - Xie, Nan; Zhu, Defeng; Xu, Qifeng; Tan, Qiao
Abstract: To achieve linear measurement of electro-optic phase delay and improve the accuracy and measurement range of the optical voltage transducer (OVT), this paper proposes a linear phase delay detection method for an optical voltage transformer based on a strip S-wave plate. Using the strip S-wave plate, the phase delay can be directly converted into the displacement of the dark stripe of the strip spot, and the displacement is located by the dual-quadrant detector. Using the Jones matrix, we confirm the linear relationship between the position of the dark stripe and the phase delay, and propose a positioning method and error compensation scheme of the dark stripe and set up an experimental system to verify its performance. The experimental results show that the OVT realizes the measurement of the electro-optic phase delay; the measuring range of the phase delay is up to ±40°, and the measurement error is less than 0.5%.